(untitled) (GAIMS Journal of Medical Sciences, 2024)
ABSTRACT Background: Elective courses, a significant addition to the competency based medical education curriculum, were implemented for the first time in the MBBS 2019 batch nationwide. This study was formulated to assess whether the design and manner of implementation of elective modules in Physiology could provide the students with diverse learning experiences. Materials and Methods: A cross-sectional study was conducted among 19 undergraduate students who completed electives in physiology at a private medical college in South India. The students enrolled in three electives in Exercise, Cardiovascular, and Sleep Physiology, each of which had a research component. Pre- and post-tests were used to assess knowledge levels in their selected topics and basics of biomedical research and a Likert scale survey was used to evaluate student perception of the electives. Pre-test and post-test scores were compared using a paired t test, and responses to survey questions were expressed in percentages using a diverging stacked bar chart. Results: Mean knowledge scores were significantly improved after the electives (p<0.05). Overall, students had a positive perception of the design, implementation, and faculty knowledge of the electives. However, some of the students reflected that data collection procedures were hectic and the daily entries of log book activities were time consuming. Conclusions: Well-designed and effectively implemented electives in physiology can provide students with valuable learning experiences, expand their knowledge, and equip them with relevant skills for their future careers. Incorporating ongoing student feedback and continuous evaluation can contribute to the refinement and improvement of future elective modules in physiology.